Factors affecting the delay of the age of marriage from the point of view of university youth - Mohammad , Osama; Akel , Magd (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This research deals with factors affecting the delay in the age of marriage among university youth (economic factor, social worker, educational worker, and security worker). This research aims to develop a general perception of the concept of youth and their characteristics and culture, Factors affecting the delay in the age of marriage, and to arrive at a set of proposals and recommendations of scientific interest in the decision-making process of marriage. One of the most prominent findings is that the decline in economic, security and social factors, respectively, negatively affects and contributes to the delay in the age of marriage, while the level of education does not affect the delayed marriage age.